Effect of Hyperbaric Oxygen Therapy on Polarization Phenotype of Rat Microglia After Traumatic Brain Injury - Liang, Fang; Kang, Nan; Li, Pinpin; Liu, Xuehua; Li, Ge; Yang, Jing (Frontiers in Neurology, 2021)
Background: The neurological defect caused by secondary damage following traumatic brain injury (TBI) is considered critical for the management of TBI. Microglia (MG) is a resident brain macrophage that could differentiate into M1 type or M2 type in response to injury and repair. It is known that the MG transition from M1 phenotype to anti-inflammatory M2 phenotype might reduce secondary injury of TBI. So, a TBI animal model was established and compared biomarkers of M1 and M2 MG between the controls and experimental animals receiving hyperbaric oxygen therapy (HBOT). This study aimed to explore whether HBOT was effective method for promoting the differentiation of MG into M2 polarized form to alleviate neurological damage after TBI. Methods: The rats were randomly divided into 4 groups: SH (Sham-operated), SH+HBO (hyperbaric oxygen), TBI, and TBI+HBO. Each group included 42 rats, and each of these were divided into 1 hour, 6 hours, 12 hours, 24 hours, 72 hours 7 days and 14 days groups. The expression of M1 biomarker inducible nitric oxide synthase (iNOS), M2 biomarker arginase 1(Arg1), associated cytokines tumor necrosis factor-α (TNF-α), and transforming growth-β1 (TGF-β1) were evaluated after the observation time. Results: TBI significantly increased the expression levels of M1 marker iNOS and M2 markers Arg1 at different time points. The increased expression of iNOS was suppressed, while the expression level of Arg1 was enhanced by HBOT. Moreover, HBOT suppressed the pro-inflammatory TNF-α secreted by M1 , and promoting the anti-inflammatory TGF-1β. Conclusions: These results suggest that HBOT can promote the recovery of neurological function by shifting the MG polarization towards the M2 phenotype following TBI.